EPIC OF GILGAMESH FROM THE EDUCATIONAL POINT OF VIEW - Бранка М. Јакшић-Провчи (Faculty of Philosophy, University of Novi Sad, City Library of Pančevo, 2011)
The paper presents an educational interpretation of the old Sumerian and Acadian epic considering its organization, the characterization of its main protaginists, and the positioning the gods within the narrative flow of the epic. Special attention is given to the phenomenon of sleep, the description of fights and fighting rivals, Gilgamesh's quest for immortality, as well as to the description of flood, and Gilgamesh's descend into the underworld.